Plasma Technology–Preparing for the Electrified Future - Cha, Min Suk; Snoeckx, Ramses (Frontiers in Mechanical Engineering, 2022)
We refer to the fourth state of matter as plasma, indicating ionized, electrically quasi-neutral gas. Electrical discharge in a gas medium is a normal and easy way of turning the gas into plasma in a moderate pressure condition. The electron temperature, electron density, and gas temperature characterize a quality of plasma. Particularly in the domain of the electron temperature and gas temperature, we have a room to design a type of discharges to be a thermal plasma (both electron and gas temperature are at around 10,000 K, an arc torch as an example) or non-thermal plasma (a couple of orders magnitude higher electron temperature than gas temperature). This indicates that a nature of plasma chemistry, consisting of electron impact reactions and thermochemistry governed by the electron temperature and gas temperature, respectively, can be tailored to a certain extent. In this regard, we think that plasmas can be considered as versatile reaction platforms, which can replace and reinforce conventional combustion and catalyst-based ones in the electrified future. This perspective particularly shares the increased opportunity for a combustion community in low-temperature plasma technology, elaborating the leashed potential of plasma chemistry and similarities with combustion studies.